ATI's MOBILITY RADEON to Power New Pentium 4 Notebook From Acer - Business Editors/Technology Writers (Business Wire, 2002)
The world's number one notebook graphics vendor, ATI Technologies (TSE:ATY, NASDAQ:ATYT), today announced that Acer's (2306.TW) powerful new notebook, the Aspire 1400 series, now includes MOBILITY(TM) RADEON(TM), the world's most popular mobile graphics processor. Copyright 2002 ATI Technologies Inc. All rights reserved. ATI and ATI product and product feature names are trademarks and/or registered trademarks of ATI Technologies Inc. All other company and product names are trademarks and/or registered trademarks of their respective owners. Features, pricing, availability and specifications are subject to change without notice.